Bacterial community composition and extracellular enzyme activity in temperate streambed sediment during drying and rewetting - Pohlon, Elisabeth; Ochoa Fandino, Adriana; Marxsen, Jürgen; Justus Liebig University Giessen (My University, 2013)
Droughts are among the most important disturbance events for stream ecosystems; they not only affect stream hydrology but also the stream biota. Although desiccation of streams is common in Mediterranean regions, phases of dryness in headwaters have been observed more often and for longer periods in extended temperate regions, including Central Europe, reflecting global climate change and enhanced water withdrawal. The effects of desiccation and rewetting on the bacterial community composition and extracellular enzyme activity, a key process in the carbon flow of streams and rivers, were investigated in a typical Central European stream, the Breitenbach (Hesse, Germany). Wet streambed sediment is an important habitat in streams. It was sampled and exposed in the laboratory to different drying scenarios (fast, intermediate, slow) for 13 weeks, followed by rewetting of the sediment from the fast drying scenario via a sediment core perfusion technique for 2 weeks. Bacterial community structure was analyzed using CARD-FISH and TGGE, and extracellular enzyme activity was assessed using fluorogenic model substrates. During desiccation the bacterial community composition shifted toward composition in soil, exhibiting increasing proportions of Actinobacteria and Alphaproteobacteria and decreasing proportions of Bacteroidetes and Betaproteobacteria. Simultaneously the activities of extracellular enzymes decreased, most pronounced with aminopeptidases and less pronounced with enzymes involved in the degradation of polymeric carbohydrates. After rewetting, the general ecosystem functioning, with respect to extracellular enzyme activity, recovered after 10 to 14 days. However, the bacterial community composition had not yet achieved its original composition as in unaffected sediments within this time. Thus, whether the bacterial community eventually recovers completely after these events remains unknown. Perhaps this community undergoes permanent changes, especially after harsh desiccation, followed by loss of the specialized functions of specific groups of bacteria.
Keywords: ddc:590